PERAN IBU SEBAGAI ORANG TUA TUNGGAL DALAM KELUARGA DI DESA GOTOWASI KECAMATAN MABA SELATAN KABUPATEN HALMAHERA TIMUR - Ibnu Rauf (HOLISTIK, Journal of Social and Culture, 2023)
The family is the only social institution that has responsibility in human development not only limited to succession but is the main and important source of education, good relationships as a family and friendship, and a level of kinship that is permanent or irreplaceable by others. Single parents are different where only the father or mother takes care of and raises their own children without the presence of a partner. It is not easy for single parents to live their lives after losing one family member, namely their husband, because everything must be borne by themselves. Taking on the role of a single parent can be caused by several things, including divorce, death, and pregnancy out of wedlock. The life of a single parent in Gotowasi Village before divorce or death by her husband, her household needs are very good because all household needs are on average provided for by her husband. But after being left behind by her husband or male head of the family, the woman then works double to support her children from the cost of daily food and drink, school fees and other needs. They seem to want to show one thing that women can live without men even though they themselves cannot deny themselves that they need a more decent family as well as the lives of others who live with complete and complete family harmony. Keywords: role, mother, single parent